Disparity in access for people with disabilities to outpatient dental care services: a retrospective cohort study - Bo-Young Park; Han-A Cho; Hosung Shin (BMC, 2023)
Abstract Background People with disabilities face difficulties in oral health management and gaining access to dental care. The availability of a regular source of dental care (RSDC) is an important factor that influences the access to health services and care management. The purpose of this study was to determine the effect of the availability of RSDC on the number of annual dental visits and dental expenses per visit among people with disabilities. Methods Data of 7,896,251 patients with dental problems in South Korea were analyzed using the 2002-2018 National Health Insurance claims data. A generalized estimating equation was applied to analyze the repeated-measurement data, and the interaction effect between RSDC and the disability severity was evaluated. Results The number of annual dental visits was higher among people with (2.62) than among those without (2.23) disabilities. Despite their increased dental needs, both annual dental visits and dental expenses per visit were low among older individuals (p < 0.001). The proportion and frequency of annual dental visits was lower among women than among men with disabilities. RSDC had differential effects on the severity of disability. Compared to people without disabilities, RSDC increased the number of annual dental visits (p = 0.067) and the dental expenses per visit (p < 0.05) among those with severe disabilities, but the effect on the number of annual dental visits was not significant among those with mild disabilities (p = 0.698). Conclusions Our results suggest a need for a special dental care system for people with disabilities, to ensure an RSDC, particularly for women and for older people with disabilities.